Estrela e matriz verde em testes de solubilidade: potencialidades para o Ensino de Química (Revista Brasileira Multidisciplinar, 2026)
Chemical activities have historically been seen as villains in environmental degradation and pollution processes. In view of this, Green Chemistry emerged as a movement that opposes polluting actions and seeks to develop processes and products that reduce or eliminate the use and generation of substances that are harmful to health and the environment. For this philosophy to become part of all dimensions of chemical activities, it is important to include this theme in the training of professionals in the field of Chemistry. This work seeks to address the potential of chemical greenness metrics, notably the holistic Green Matrix and Green Star, applied to solubility tests as a proposal to corroborate the inclusion of Green Chemistry in Chemistry Education. The experimental results of the Green Star and Green Matrix helped to identify the strengths and weaknesses of the experiments based on the principles of Green Chemistry, as well as to glimpse opportunities for improvements, such as the reduction and replacement of reagents that are harmful to health and the environment with greener substances, as well as highlighting the threats related to the use of volatile and toxic solvents under heating.